2006
DOI: 10.17221/3924-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary sodium selenite, Se-enriched yeast and Se-enriched Chlorella on egg Se concentration, physical parameters of eggs and laying hen production

Abstract: ISA Brown laying hens at 24 weeks of age, housed in laying battery cages, were used in this 4-group experiment. One group was fed a basal diet containing primarily maize, soybean meal and wheat. Selenium (Se) content of the basal diet was 0.07 mg/kg dry matter. The other hens received diets supplemented with Na 2 SeO 3 , Se-enriched yeast and Se-enriched alga Chlorella, respectively, in a concentration of 0.3 mg Se/kg. The experiment lasted twenty-seven weeks. Egg production, feed consumption, egg weight, phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
52
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 15 publications
12
52
0
3
Order By: Relevance
“…Experimental groups with Se-yeast (at the dose of 0.4 mg/kg and 0.9 mg/kg DM) differed significantly from the control group (P<0.05). Similar increase of eggs weight after administration of selenium, especially in the form of Se-yeast, was reported also by other authors [7,11]. Beneficial effect of inorganic selenium with the supplement of vitamin E on the egg weight was reported [9].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Experimental groups with Se-yeast (at the dose of 0.4 mg/kg and 0.9 mg/kg DM) differed significantly from the control group (P<0.05). Similar increase of eggs weight after administration of selenium, especially in the form of Se-yeast, was reported also by other authors [7,11]. Beneficial effect of inorganic selenium with the supplement of vitamin E on the egg weight was reported [9].…”
Section: Resultssupporting
confidence: 83%
“…Organic selenium increases egg production, improves fertility, antioxidant status, accelerating of feathers growth after feather loosing of layers at saddle and back sections [4] and has positive influence on storage ability of eggs. Selenium concentration in eggs according to many authors was markedly higher in groups with organic selenium [7,14,11,12]. In experiment of [2] human volunteers receiving multiple-enriched eggs improved the blood concentration of omega-3 fatty acids, HDL cholesterol, LDL cholesterol and triglycerides.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation of Se influences quality traits of poultry products (Skřivan et al, 2006;Arpášová et al, 2009). Se is a structural component of glutathione peroxidase (GSH-Px, E.C.1.11.1.9), which catalyzes the reduction of hydrogen peroxide and organic hydroperoxides, thus protecting the cells from oxidative damage.…”
mentioning
confidence: 99%
“…The results of the study of Utterback et al (2005) indicated that the use of Se-yeast in laying hen diets was very effective for increasing the Se content of eggs. Skřivan et al (2006) investigated the effect of dietary sodium selenite, Se-enriched yeast and Se-enriched alga Chlorella on Se concentration in eggs, physical parameters of eggs and laying hen production. They reported higher utilization of the organic form of selenium from Se-enriched yeast and Se-enriched alga Chlorella in laying hens compared to the inorganic form of selenium (Na 2 SeO 3 ).…”
mentioning
confidence: 99%